Prospects for trade in high-tech products between Ukraine and Japan, The People's Republic of China and The Republic of Korea in the conditions of the new industrial revolution - Matiushenko, Ihor; Gavrilova, Katerina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
Introduction. Today in the context of the deployment of the fourth industrial revolution for developing countries (such as Ukraine) the problem of preserving and increasing exports of high-tech products in the conditions of curtailment of production is exacerbated. The question of determining the prospects for the development of trade in high-tech products between Ukraine and the Asian countries-leaders by 2020is extremely relevant. Materials and Methods. Methods of statistics, morphological and logical analysis, comparative studies, and correlation-regression analysis have been used for the purpose of research. Results.As result of the study, it has been established that Ukraine has comparative advantages in trade with Japan, China and the Republic of Korea in such groups of goods as air floats and spacecraft, as well as medical equipment and optical instruments. On basis of correlation-regression analysis, relationships between factors were identified and regressive models of foreign trade of high-tech goods of the studied countries were constructed. Recommendations for increasing the efficiency of trade in high-tech goods of Ukraine with Japan, China and the Republic of Korea are developed. Conclusion.For increase Ukraine's high-tech exports to leading Asian countries - technological leaders, it is expedient to implement the following measures: (1) state support and encouragement of private and state-owned enterprises to high-tech production; (2) creation of "technological infrastructure" by adapting education to the current needs of production, developing industrial clusters, etc.; (3) increasing the competitiveness of Ukrainian high-tech exports, especially those sectors where comparative advantages were found; (4) searching for opportunities to enter new markets.